Intercultural Communication, International Context, and Translation Competence: An Academic Improvement Proposal for Translation Programs in Chile [Comunicación Intercultural, Contexto Internacional y Competencia Traductora: Una Propuesta de Mejora Académica Para Los Programas de Traducción en chile1 - Ahumada-Figueroa, M; Basaure-Cabero, R (UCOPress. Cordoba University Press (UCOPress Editorial Universidad de Córdoba), 2021)
The need for communication not only crosses physical boundaries, but also virtual ones. In this sense, translation has always been the means to establish this interaction, and today more than ever reality projects the professionals of the field as key agents in the intercultural mediation among different realities. Academic institutions are aware of the translators’ historical role in the development of the international community and the training requirements that current reality brings with it. However, within the curricular guidelines - particularly within Chilean case - it is evident that translation competence areas related to this context and the role of translation in this field is not a priority aspect, despite the fact that this topic is at the forefront of international disciplinary research. In this sense, this paper aims to analyze this issue from the Chilean perspective, in order to examine the curricular guidelines from the academic-training point of view as well as from the future development of disciplinary research. Methodologically, the research explores the relationship between Chile s need for intercultural communication and the educational curricula of the institutions and proposes guidelines for future translators in terms of curriculum and professional training. The relationship between interculturality and translation competence is presented to continue with the analysis of Chilean curricula and concluding with a proposal that considers this aspect as a formative axis by developing content related to the international relations context, as part of professional training. The article concludes that a flexible curriculum capable of providing specialized knowledge will allow future professionals to face the challenges of a changing socio-cultural context, proposal that could be considered by the rest of the academic programs in the region. © 2021 Universidad de Cordoba,Servicio de Publicaciones. All rights reserved.